Caregiver psychological burden of RSV Hospitalization of children 2 years of age and under - Lazarus Adua; Krow Ampofo; Evan Heller; Per Gesteland; Abbey Loveridge; Katherine Werdan; Kaleb Miller; Alex Platt-Koch; Madelyn Ruggieri; Lyn Finelli; Yoonyoung Choi (PLoS ONE, 2025)
Objectives Caregiver psychological burden has been reported among premature children hospitalized with respiratory syncytial virus (RSV) infection. This study addresses two objectives: 1) assessing the psychological burdens of stress and anxiety among caregivers of otherwise healthy children 2 years of age and under hospitalized with RSV lower respiratory tract infection (LRTI); and 2) analyzing sociodemographic and clinical factors related to these psychological burdens. Study Design We prospectively recruited caregivers of children ≤2 years of age hospitalized with RSV LRTI at Primary Children’s and Riverton Hospitals, Salt Lake City, Utah, during the 2019–2022 RSV seasons. Data came from a survey that included the Parental Stress Scale (PSS) and the State-Trait Anxiety Inventory for Adults (STAIAD) and patients’ medical records. Relationships between sociodemographic and clinical factors and caregiver stress and anxiety were assessed using linear regression models. Results In all, 146 caregivers completed the survey in-hospital and 109 at 2 weeks post-discharge. Substantial levels of stress and anxiety were observed. Over 50% rated more than half of the PSS items as very or extremely stressful, and over 80% rated three specific items as extremely stressful: 87% felt helpless about how to help their child, 85% were concerned about their child’s unusual breathing, and 81% felt unable to protect their child from pain and painful procedures. On most STAIAD items, we observed an increase in positive outlook and a decrease in negative outlook items between hospitalization and two weeks post-discharge, with the greatest change seen in reduced worry about things that don’t matter. Caregiver’s increased stress and anxiety were significantly associated with Hispanic ethnicity, non-White race, lower household income, and more intensive respiratory support types. Household income was an important factor influencing the relationship between ethnicity and caregiver stress and anxiety. Conclusions The hospitalization of children ≤2 years of age with RSV lower respiratory tract infection remains a major source of psychological burden on caregivers. The difference in burden by ethnicity, race and income identified highlights the importance of seeking equity in the distribution of RSV immunoprophylaxis and maternal vaccines for prevention.